Film Mini Televisi: Alternatif Menghadirkan yang Kecil di Tengah yang Besar - Utami, Thesa Resi Sila; -, Handriyotopo (Capture : Jurnal Seni Media Rekam, 2011)
Television drama in Indonesia are almost dominated by soap operas. The story themes often lifted beyond the reality of society, and even tend to be exaggerated. The scenes and dialogue have sexist, rude, filthy and indecent language spoken by the children actors. Ambiguity plot, theme, and segmentation will direct the public mindset, a fictional drama on television is no longer a positive impact impressions but rather a negative influence. Screenplay is absolutely necessary to facilitate television programs production team for communicating everything related to the creative process of copywriting for film and television drama. Besides, television drama is also expected to present certain value espesially social responsibility and learning.Â Key words: film, miniseries, screenplay, drama, television